Presence of Segmented Filamentous Bacteria in Human Children and Its Potential Role in the Modulation of Human Gut Immunity - Chen, Bo; Chen, Huahai; Shu, Xiaoli; Yin, Yeshi; Li, Jia; Qin, Junjie; Chen, Lijun; Peng, Kerong; Xu, Fei; Gu, Weizhong; Zhao, Hong; Jiang, Liqin; et al. (Frontiers in Microbiology, 2018)
Segmented filamentous bacteria (SFB) are commensal organisms which grow by anchoring a specialized holdfast structure to the intestinal walls of a variety of animals. Interaction of SFB with Peyer’s patches in mice promotes the post-natal maturation of the immune system. We previously reported that the colonization of SFB in humans mainly occurs by 36 months of age, and is difficult to be detected afterwards. In this study, we measured the level of SFB in intestinal fluids of human children. SFB were found via qPCR to represent a small fraction of the whole SFB-positive microbiota (105 SFB in 1011 total bacteria). Bacteria with filamentous segmented morphology were observed in intestinal fluids via fluorescent in situ hybridization, and from gut biopsies via scanning electron microscopy. SFB-specific DNA and peptide fragments were also identified via multiple displacement amplification PCR and mass spectrometry. There was an overall positive correlation between the presence of SFB and the titer of total secretory immunoglobulin A (sIgA), which is more apparent in intestinal fluids of the age group of 8-36 months. Afterwards there was a decline of SFB in numbers correlated with a reduction of total sIgA. RT-qPCR analysis of the terminal ileal biopsies revealed that the expression of Th17 pathway genes were induced in SFB-positive samples, while the markers of T and B cell receptor signaling pathways were also upregulated. Collectively, these data suggest that SFB is a rare member of microbiota, and may play an important role in the development of human gut immunity.